2020
DOI: 10.1038/s41467-020-15616-y
|View full text |Cite
|
Sign up to set email alerts
|

Atomic imaging of mechanically induced topological transition of ferroelectric vortices

Abstract: Ferroelectric vortices formed through complex lattice–charge interactions have great potential in applications for future nanoelectronics such as memories. For practical applications, it is crucial to manipulate these topological states under external stimuli. Here, we apply mechanical loads to locally manipulate the vortices in a PbTiO3/SrTiO3 superlattice via atomically resolved in-situ scanning transmission electron microscopy. The vortices undergo a transition to the a-domain with in-plane polarization und… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
36
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 46 publications
5
36
0
2
Order By: Relevance
“…2c acquired from a region that only includes the (PTO) 10 /(STO) 10 superlattice layers. It reveals superlattice reflections both in-plane and out-of-plane, from which the in-plane lattice parameter a and out-of-plane lattice parameter c are calculated to be ~3.9 Å and ~4.0 Å, similar to those observed in reference 40 40 . In particular, the enlarged view of satellite diffraction spots around (001) reflection (inset in Fig.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…2c acquired from a region that only includes the (PTO) 10 /(STO) 10 superlattice layers. It reveals superlattice reflections both in-plane and out-of-plane, from which the in-plane lattice parameter a and out-of-plane lattice parameter c are calculated to be ~3.9 Å and ~4.0 Å, similar to those observed in reference 40 40 . In particular, the enlarged view of satellite diffraction spots around (001) reflection (inset in Fig.…”
Section: Resultssupporting
confidence: 78%
“…We also calculated the corresponding tetragonality in terms of c / a ratio (Fig. 2e ), wherein the red sinusoidal wave-like pattern also suggests the vortex pair as previously reported 8 , 38 40 . Pairs of clockwise and anticlockwise vortices are schematically shown in Fig.…”
Section: Resultssupporting
confidence: 63%
“…Du et al (30) reported that vortices can split, transform to polar waves, and finally become a stable c domain that does not recover spontaneously. According to Chen et al (31), under mechanical stress, a polar vortex can be switched to an a domain and reversibly recover after removal of stress. In our study, the switching behaviors of flux-closures are even more complicated than those of vortices, because the transformation of a flux-closure involves not only the topological core but also the ordinary ferroelectric 90°and 180°domain walls.…”
Section: Discussionmentioning
confidence: 99%
“…Phase-field simulations have demonstrated the possibility of switching polar vortices: under the application of an electrical field, vortex cores with opposite curls move closer until they reach the same lateral position and then produce new a domains, and the reverse process of back-switching takes place when the applied field is removed ( 37 ). The evolution of vortices driven by temperature change ( 29 ), electric field, and stress have been probed experimentally by X-ray diffraction, PFM ( 29 ), and TEM ( 30 , 31 ). Damodaran et al ( 29 ) found phase coexistence of vortex and ferroelectric phases and electric-field-driven interconversion between them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation